Treatment with Cefotaxime Affects Expression of Conjugation Associated Proteins and Conjugation Transfer Frequency of an IncI1 Plasmid in Escherichia coli - Møller, Thea S. B.; Liu, Gang; Boysen, Anders; Thomsen, Line E.; Lüthje, Freja L.; Mortensen, Sisse; Møller-Jensen, Jakob; Olsen, John E. (Frontiers in Microbiology, 2017)
Horizontal gene transfer (HGT) is the major mechanism responsible for spread of antibiotic resistance. Antibiotic treatment has been suggested to promote HGT, either by directly affecting the conjugation process itself or by selecting for conjugations subsequent to DNA transfer. However, recent research suggests that the effect of antibiotic treatment on plasmid conjugation frequencies, and hence the spread of resistance plasmids, may have been overestimated. We addressed the question by quantifying transfer proteins and conjugation frequencies of a blaCTX-M-1 encoding IncI1 resistance plasmid in Escherichia coli MG1655 in the presence and absence of therapeutically relevant concentrations of cefotaxime (CTX). Analysis of the proteome by iTRAQ labeling and liquid chromatography tandem mass spectrometry revealed that Tra proteins were significantly up-regulated in the presence of CTX. The up-regulation of the transfer machinery was confirmed at the transcriptional level for five selected genes. The CTX treatment did not cause induction of the SOS-response as revealed by absence of significantly regulated SOS associated proteins in the proteome and no significant up-regulation of recA and sfiA genes. The frequency of plasmid conjugation, measured in an antibiotic free environment, increased significantly when the donor was pre-grown in broth containing CTX compared to growth without this drug, regardless of whether blaCTX-M-1 was located on the plasmid or in trans on the chromosome. The results shows that antibiotic treatment can affect expression of a plasmid conjugation machinery and subsequent DNA transfer.